Spatial distribution of Mycobacterium ulcerans in Buruli ulcer lesions: implications for laboratory diagnosis - Ruf, Marie-Thérèse; Vogel, Moritz (PLoS neglected tropical diseases, 2016)
Currently, four laboratory methods are available to diagnose Buruli ulcer, a neglected tropical skin disease caused by Mycobacterium ulcerans affecting mainly children in remote rural areas of West Africa. Only one of the four methods, direct microscopic examination of wound exudate for acid fast bacilli, is suitable as point-of-care test. The others, histopathology, culture and IS2404 quantitative PCR, require sophisticated laboratory infrastructure. However, in comparison to the current gold standard, IS2404 quantitative PCR, microscopic smear examination has limited sensitivity. Our results on the distribution of M. ulcerans in Buruli ulcer lesions emphasize that the sensitivity of Buruli ulcer laboratory diagnosis is dependent on optimal sampling procedures. Accurate histopathology crucially depends on tissue samples containing all three skin layers, including the subcutis in which the majority of the bacteria are found. For IS2404 quantitative PCR, culture and direct smear detection, the margin of ulcerative lesions should be sampled at several positions, since bacteria and bacterial DNA are unevenly distributed. With optimized sampling, well-trained laboratory personnel and good microscopy infrastructure, direct smear examination reached a sensitivity of 73%, as compared to IS2404 quantitative PCR.